Diversifying readership through open access: A usage analysis for open access books - Pyne, Ros (Septentrio Conference Series, 2020)
In 2019 Springer Nature worked with COARD to analyse usage data relating to almost 4,000 books, including 281 OA books. Our goal was to better understand the extent to which usage of OA books differs from usage of closed books, looking not only at the number of downloads but also at their geographical distribution. The findings show that for every book type, every discipline and across all time since publication, OA books are reaching more readers, in more countries, including more readers in low- and lower-middle-income countries.